CODE BLUE: WHAT TO DO? - Porteous, Joan (Operating Room Nurses Association of Canada Journal, 2009)
Cardiac arrest may occur intraoperatively at any time. The purpose of this article is to help the reader recognize and assist in the management of an intraoperative cardiac arrest. Patients who are at risk for cardiac arrest in the OR are identified and different types of pulseless arrythmias are identified. Roles of perioperative personnel are suggested and documentation during the code is discussed.